2022
DOI: 10.1177/09567976211063912
|View full text |Cite
|
Sign up to set email alerts
|

Early Adolescents Demonstrate Peer-Network Homophily in Political Attitudes and Values

Abstract: Research on political homophily has almost exclusively focused on adults, and little is known about whether political homophily is present early in life when political attitudes are forming and friendship networks are rapidly changing. We examined political homophily using a social network approach with rural middle school students ( N = 213; mean age = 12.5 years; 57% female) from a remote U.S. community. Preregistered analyses indicated that early adolescents were more likely to spend time with people who sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
1
7
1
Order By: Relevance
“…Individuals in these rural communities do not appear to consider political differences to be an important dimension on which friendship decisions should be based. This finding stands in contrast to what has been observed in many Western and industrialised settings, where convergent political opinions seem to be important for creating and maintaining both social and romantic relationships (e.g., Huber and Malhotra, 2017;Oosterhoff, Poppler and Palmer).…”
Section: Discussioncontrasting
confidence: 97%
“…Individuals in these rural communities do not appear to consider political differences to be an important dimension on which friendship decisions should be based. This finding stands in contrast to what has been observed in many Western and industrialised settings, where convergent political opinions seem to be important for creating and maintaining both social and romantic relationships (e.g., Huber and Malhotra, 2017;Oosterhoff, Poppler and Palmer).…”
Section: Discussioncontrasting
confidence: 97%
“…Critical consciousness research has found that marginalization experienced by youth of color can shape broader perceptions of inequities in society (Bañales & Rivas-Drake, 2022;Diemer & Rapa, 2016), which could partially explain the social relevance of awareness of inequities in the current sample of mostly low-income adolescents of color. More broadly, the findings that youth tend to be friends with peers who share similar civic attitudes are consistent with studies of political orientation of adults (e.g., Huber & Malhotra, 2017) and aligned with a similar social network study that uncovered homophily on civic beliefs among middle school students (Oosterhoff et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…Friendships in high schools are an important medium for political influence and the development of critical consciousness (Diemer & Li, 2011), although much remains unknown about the associations between peer relationships and diverse forms of civic participation. Youth tend to associate with peers who share similar characteristics (“homophily”; McPherson et al, 2001) and civic homophily has increasingly attracted attention as a subject of research (Oosterhoff et al, 2022; Passe et al, 2018), in part due to the unprecedented political polarization that has permeated school environments in recent years (Kennedy et al, 2020). Scholars have long recognized that adult friendship groups are more politically homogenous than one would predict by chance (Verbrugge, 1977); yet, research on youth is lacking, despite the importance of adolescent experiences in shaping political attitudes throughout adulthood (Russo & Stattin, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socialization processes are relevant to a variety of traditionally adaptive and maladaptive behaviors (Laursen, 2018). Recent work suggests that peer influence effects are present in prosocial behavior and attitudes (Carlo & Padilla‐Walker, 2020; Choukas‐Bradley et al., 2015; Crone et al., 2022), the formation of political opinions (Oosterhoff et al., 2022), and improved academic performance (Duxbury & Haynie, 2020), and these effects may be particularly strong during adolescence (Foulkes et al., 2018). The majority of work to date, however, has examined the socialization of dangerous, illegal, and health‐risk behaviors, including aggression, substance use, sexual risk, and self‐injurious behaviors (Brechwald & Prinstein, 2011; Montgomery et al., 2020).…”
mentioning
confidence: 99%